Implementasi Algoritma Aes-128 Untuk Pengamanan Text Dalam Sistem Keamanan Data - Djami, Dorkas; Ninu, Irene; Naitkakin, Petronela Tati; Priangan, Novianti Rosana; Blaang, Angelica Apriani Diane (PT. Publikasiku Academic Solution, 2025)
In the midst of the development of digital technology, information protection is a top priority to ensure data confidentiality. One of the proposed solutions is the implementation of the Advanced Encryption Standard (AES) algorithm with 128-bit keys (AES-128) as a method of text encryption. This algorithm was chosen for its process speed and ability to generate a high layer of security through a combination of complex mathematical operations. The research developed a graphical interface (GUI)-based system to test AES-128's performance in encrypting and decrypting text data. The results of the experiment proved that this algorithm is capable of generating random ciphertext that cannot be returned to its original form without a valid decryption key. In addition, the encryption-decryption process remains efficient even though the data size increases due to the addition of padding. These findings confirm that AES-128 is a great choice for improving the security of digital information exchange systems.